State violence and punishment in India - Sherman, Taylor C. (Royal Asiatic Society books, 2010)
Introduction : state violence and punishment in India, 1919-56 -- Jallianwala Bagh, the Punjab disturbances of 1919, and the limits of state power in India, 1919-20 -- Disobedience and discord : the non-cooperation movement, 1920-25 -- Extra-judicial punishments and the civil disobedience movement, 1930-34 -- Legislating against communal violence : the United Provinces Goonda Act and the Bombay Whipping Act, 1929-38 -- The hunger strikes of the Lahore Conspiracy Case prisoners, 1929-39 -- The Second World War and India's coercive network, 1939-46 -- Partition and the transitional state in India, 1947-48 -- The police action in Hyderabad and the making of the postcolonial state in India, 1947-56 -- Conclusion : rethinking colonial punishment, reassessing postcolonial India